A Wheat WRKY Transcription Factor TaWRKY46 Enhances Tolerance to Osmotic Stress in transgenic Arabidopsis Plants - Li, Xiaorui (Int J Mol Sci, 2020)
WRKY transcription factors play central roles in developmental processes and stress responses of wheat. Most WRKY proteins of the same group (Group III) have a similar function in abiotic stress responses in plants. TaWRKY46, a member of Group III, was up-regulated by PEG treatment. TaWRKY46-GFP fusion proteins localize to the nucleus in wheat mesophyll protoplasts. Overexpression of TaWRKY46 enhanced osmotic stress tolerance in transgenic Arabidopsis thaliana plants, which was mainly demonstrated by transgenic Arabidopsis plants forming higher germination rate and longer root length on 1/2 Murashige and Skoog (MS) medium containing mannitol. Furthermore, the expression of several stress-related genes (P5CS1, RD29B, DREB2A, ABF3, CBF2, and CBF3) was significantly increased in TaWRKY46-overexpressing transgenic Arabidopsis plants after mannitol treatment. Taken together, these findings proposed that TaWRKY46 possesses vital functions in improving drought tolerance through ABA-dependent and ABA-independent pathways when plants are exposed to adverse osmotic conditions. TaWRKY46 can be taken as a candidate gene for transgenic breeding against osmotic stress in wheat. It can further complement and improve the information of the WRKY family members of Group III.